Criminal law and criminal justice: morals and policy - Elkington, Amy (Routledge, 2025)
"Criminal Law and Criminal Justice: Morals and Policy goes beyond the traditional criminal law textbook and invites students to question why we criminalise certain behaviour and whether the decisions made by the courts can be justified according to legal principle, morals and policy. Providing an overview not only of the legal doctrine of criminal law, but also of the underpinning theory behind the legal doctrine, the book encourages critical thinking around the context behind, and implementation of, legal decisions. It applies this to current issues, such as respect for personal autonomy, prevention of domestic abuse and discouraging gang activity, whilst providing a clear overview of the law relating to actus reus, mens rea, property offences, homicide, non-fatal offences, sexual offences, accessorial liability, and defences. Using hypothetical scenarios, students will develop an understanding of why certain rules exist and then be able to critically analyse why certain behaviour is criminalised. An in-depth study of several key cases will show how the rules and theory play out in practice, and students will examine how morals and policy have influenced these decisions. Featuring thinking points as well as further reading suggestions, this textbook is suitable for all students of criminal law, as well as for those studying jurisprudence"--